A inserção e permanência de crianças e adolescentes no projeto social esporte para todos: uma análise a partir da Organização da sociedade civil oficina escola de Lutheria da Amazônia - Maciel, Laiana Fernandes (Brasil, 2022)
The general objective of this research is to analyze the social context of the insertion and permanence of children and adolescents in the project Esporte Para Todos (Sport for All), coordinated by the Institution Oficina Escola de Lutheria da Amazônia. The relevance is justified by the importance that social projects of this type have contributed not only to the lives of children and adolescents, but the community in general. The Third Sector has been gaining great proportion in civil society and has shown itself as one of the protagonists in social projects focused on the area of children and adolescents. The study made it possible to observe that the social projects developed by Civil Society Organizations (CSOs), especially the one contemplated in this study, play an important role in development of social actions aimed at people living in poverty. They are non-profit Civil Society Organizations, such as the Luther School Workshop of the Amazon (OELA), which work with social project initiatives that have contributed to changing the life perspectives of many children and adolescents. As for the methodological procedures, the study was developed through bibliographic and documentary reviews, which included analysis of monthly reports of the Sport for All project, the institution's annual report and social diagnosis to learn about the socio- historical and economic reality of the children and adolescents served by OELA and characterize, through these documents, the challenges these children or adolescents had in their daily lives.